Professional Orientation of Teaching Ethnology in the System of Ukrainian Philologists Preparation - Olesya Bartashuk (Pedagogical Discourse, 2012)
Peculiarities of teaching social-humanitarian discipline “ethnology” in the aspect of professional orientation of Ukrainian philologists preparation are analysed in the article; attention is paid to inter-discipline connections of ethnology and Ukrainian literature.